2022
DOI: 10.3390/ma15082834
|View full text |Cite
|
Sign up to set email alerts
|

Dry Sliding Tribological Behaviors of Electrodeposited Ni-GO/SiC Composite Coating on the 2218 Aluminum Alloy

Abstract: Electrodeposition has attracted tremendous interest in functional coatings due to its advantages of high efficiency, inexpensiveness and ease of implementation. In this work, nickel graphene oxide (Ni-GO), nickel silicon carbide (Ni-SiC) and nickel graphene oxide/silicon carbide (Ni-GO/SiC) composite coatings were electrodeposited on the 2218 aluminum alloy (2218AlA) substrate. The microstructure, microhardness, bonding strength and tribological behaviors of the composite coatings were carried out. According t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…To solve the above problems, surfactants are usually added to the bath to change the surface hydrophobicity of particles [8]. For example, Yan et al [9] used sodium dodecyl sulfate (SDS) to disperse SiC nanoparticles in a Ni bath, and a uniform Ni/SiC composite coating was obtained that achieved a hardness of 407.76 Hv. Ger et al [10] reported that the addition of cetyltrimethylammonium bromide (CTAB) could reduce the agglomeration of SiC particles in the plating bath and improve the hardness of Ni/SiC composite coatings.…”
Section: Introductionmentioning
confidence: 99%
“…To solve the above problems, surfactants are usually added to the bath to change the surface hydrophobicity of particles [8]. For example, Yan et al [9] used sodium dodecyl sulfate (SDS) to disperse SiC nanoparticles in a Ni bath, and a uniform Ni/SiC composite coating was obtained that achieved a hardness of 407.76 Hv. Ger et al [10] reported that the addition of cetyltrimethylammonium bromide (CTAB) could reduce the agglomeration of SiC particles in the plating bath and improve the hardness of Ni/SiC composite coatings.…”
Section: Introductionmentioning
confidence: 99%